PERSIAPAN PERSALINAN DAN KELAHIRAN DI MASA PANDEMI COVID-19 - Asiah, Asiah; Lubis, Melinda Rosa; Purba, Yani Aprilia (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2021)
The COVID-19 pandemic has had an impact on all aspects, one of which is the Health aspect which has resulted in limited face-to-face activities with health workers in Antenatal Care (ANC) services. This creates anxiety for pregnant women in facing their labor and birth. Based on these conditions, community service is carried out by socializing the improvement and knowledge of pregnant women about preparation for labor and birth during the COVID-19 pandemic. The implementation of the socialization was carried out with 2 approaches, namely an online survey with e-form via WhatsApp media and directly meeting pregnant mothers from house to house which of course was carried out according to the COVID-19 Health protocol. Ahmad et al., (2021) The results of the survey were found in the group that used the google form of pretest knowledge, the average value of 49% increased after the posttest to 89%. Meanwhile, in the group who visited the pretest knowledge house, the results showed an increase of 47% after the posttest to 87%. The implementation of this service went smoothly because it was supported by the government and the surrounding community. In the future, it is hoped that this kind of socialization can be implemented by stakeholders in handling and making health policies related to health services for pregnant women during the current pandemic. Rokhamah, (2019)